2015
DOI: 10.1080/00918369.2015.1060053
|View full text |Cite
|
Sign up to set email alerts
|

It’s Not Me, It’s You: Perceptions of Partner Body Image Preferences Associated With Eating Disorder Symptoms in Gay and Heterosexual Men

Abstract: This study explored perceptions of partner body image preferences and symptoms of disordered eating in gay and heterosexual men. Participants were male college students (n = 201; M age = 20.46), and over one third identified as gay. We compared discrepancies between participants' current and ideal body type and participants' current body type and the body type they believed they should have to attract a dating partner. For gay men, the discrepancy between their current body and the body they believed they shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
11
0
1
Order By: Relevance
“…Furthermore, for gay adults, the discrepancy between current body shape and the body shape they believed they should have to attract a partner was significantly greater than their current body shape and ideal body shape. This discrepancy is associated with greater eating, shape, and weight concerns, suggesting that beliefs of partner body image preferences contribute to disordered eating behaviors in gay adults [ 57 ].…”
Section: Eating Disorders and Disordered Eating Behaviors Within Lgbtmentioning
confidence: 99%
“…Furthermore, for gay adults, the discrepancy between current body shape and the body shape they believed they should have to attract a partner was significantly greater than their current body shape and ideal body shape. This discrepancy is associated with greater eating, shape, and weight concerns, suggesting that beliefs of partner body image preferences contribute to disordered eating behaviors in gay adults [ 57 ].…”
Section: Eating Disorders and Disordered Eating Behaviors Within Lgbtmentioning
confidence: 99%
“…Restrictive dieting (n = 19).-Seventeen studies found that sexual minority males reported higher rates of restrictive dieting and fasting during adolescence and young adulthood compared to heterosexual males (Ackard, Fedio, Neumark-Sztainer, & Britt, 2008;S. B. Austin et al, 2004;Calzo et al, 2015;Conner, Johnson, & Grogan, 2004;Dakanalis et al, 2012;Fussner & Smith, 2015;Gettelman & Thompson, 1993;Hadland, Austin, Goodenow, & Calzo, 2014;Laska et al, 2015;Li, Smith, Griskevicius, Cason, & Bryan, 2010;Lipson & Sonneville, 2017;Matthews-Ewald, Zullig, & Ward, 2014;Shearer et al, 2015;Siever, 1994;Smith, Hawkeswood, Bodell, & Joiner, 2011;Strong, Williamson, Netemeyer, & Geer, 2000;Watson, Adjei, Saewyc, Homma, & Goodenow, 2017). French and colleagues (1996) found sexual minorities and heterosexuals did not differ in the likelihood of restrictive dieting, and the other study utilized a female-only sample (Striegel-Moore, Tucker, & Hsu, 1990).…”
Section: Disordered Eating Behaviorsmentioning
confidence: 99%
“…).-In this review, "body image" was used as a catchall term comprising items like body dissatisfaction and weight perception. Among males, two-thirds (n = 12) of studies indicated sexual minorities reported worse overall body image compared to heterosexuals (Austin et al, 2004;Carper et al, 2010;Conner et al, 2004;Dakanalis et al, 2012;French et al, 1996;Fussner & Smith, 2015;Laska et al, 2015;Li et al, 2010;Siever, 1994;Smith et al, 2011;Strong et al, 2000;VanKim et al, 2016). During adolescence, weight perception relative to BMI emerged as an important construct.…”
Section: Body Image (N = 18mentioning
confidence: 99%
See 1 more Smart Citation
“…Sociocultural theories emphasize the importance of sexual minority community norms concerning appearance, and minority stress theory posits that sexual orientation‐related discrimination, victimization, and self‐stigma lead to disproportionate levels of stress in sexual minority groups, which contribute to elevated ED risk (Calzo, Blashill, Brown, & Argenal, 2017). Evidence indicates sexual minority males may experience more appearance pressures than their heterosexual peers (Fussner & Smith, 2015), while sexual minority females may not (Dotan, Bachner‐Melman, & Dahlenburg, 2019). Therefore, a sociocultural perspective might predict elevated ED risk only in sexual minority males, whereas a minority stress perspective might predict elevated ED risk in both male and female sexual minorities.…”
Section: Introductionmentioning
confidence: 99%